(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This study examines the relationship between price liberalization and supply chain efficiency in Nigeria’s downstream petroleum sector. For decades, Nigeria operated a fuel subsidy regime characterized by administered pricing, fiscal strain, and persistent supply distortions. The 2023 subsidy removal marked a structural shift toward market-determined pricing, with potential implications for operational performance within the petroleum distribution network. Drawing on the Resource-Based View (RBV), the study posits that liberalized pricing increases firms’ exposure to real cost conditions, thereby intensifying reliance on internal logistics capabilities and resource optimization. Using a cross-sectional survey design, data were collected from 279 stakeholders across Nigeria’s downstream petroleum distribution chain. Pearson Product Moment Correlation analysis was employed to assess the relationships between price liberalization and two dimensions of supply chain efficiency: product availability and cost efficiency. The findings reveal a strong positive relationship between price liberalization and product availability (r = 0.684, p < 0.05) and a moderate-to-strong positive relationship with cost efficiency (r = 0.643, p < 0.05). The results suggest that market-based pricing reforms are associated with improved operational discipline and enhanced supply chain performance. The study contributes empirical evidence linking pricing reform to firm-level efficiency outcomes in a developing oil-producing economy and offers policy-relevant insights for sustaining efficiency gains under liberalized regimes.